Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Deep organic fertilization reshapes C: N:P stoichiometry and spatial microbial distribution in semi-arid vineyard soils - Komlanvi Jacob Maneh; Louis A Tremblay; Akpene Nassougou; Gregory S.K. Zackariah; Okbagaber Andom; Yohannes Kebede; Ting Du; Shuxian An; Zhaojun Li (Journal of Soils and Sediments, 2026)

The Siwaliks: Reading Rodent Evolution in the Miocene of South Asia - Catherine Badgley; John Barry; Anna K. Behrensmeyer; Lawrence J. Flynn; Louis L. Jacobs; Yuri Kimura; Michèle E. Morgan; David Pilbeam; S. Mahmood Raza; Nikos Solounias (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The frailty mortality link in people with chronic diseases pertaining to 13 body organ systems: findings from the UK Biobank study - Justine Dastouet; Aurore Fayosse; Louis Jacob; Archana Singh-Manoux; Séverine Sabia; Benjamin Landré (GeroScience, 2025)
Frailty in older adults, particularly those with chronic diseases, has a robust association with risk of mortality, but whether this is the case in middle-aged adults is unclear. We examined the frailty-mortality association in middle-aged adults with chronic diseases and multimorbidity. Data on Fried’s frailty phenotype (robust, prefrail, frail) and 47 chronic diseases, mapped to 13 body organ systems, was available on 230,960 participants of the UK Biobank study (mean age 57.8, range 38.0–72.0). The mortality follow-up was 13.3 (± 2.1) years, and associations with mortality were examined using Cox regression, adjusted for socio-demographic factors and health behaviours. Compared to the robust group, frailty (HR, 2.32 (95% confidence intervals, 2.21; 2.43)) and prefrailty (1.35 (1.31; 1.39)) in those with diseases in any body organ system had a higher risk of mortality. Frailty was associated with a higher mortality risk for all 13 groups (all p < 0.01); estimates ranged from 2.25 (2.12; 2.39) for circulatory system diseases to 2.97 (2.60; 3.39) for the eye system. The same was the case for prefrailty; estimates ranged from 1.33 (1.23; 1.43) to 1.61 (1.03; 2.51). Between 19 and 34% of the mortality risk in the 13 disease groups could potentially be explained by frailty/prefrailty. Frailty ( p < 0.01) and prefrailty ( p < 0.01) had stronger associations with mortality in those with diseases affecting multiple organ systems. These findings highlight the importance of frailty in middle-aged adults with chronic diseases, suggesting that a third of the excess risk of mortality could potentially be addressed by improving frailty status.

Role of age in the association of chronic conditions and multimorbidity with incident ADL disability: multicohort analyses of 108,810 adults - Benjamin Landré; Aurore Fayosse; Louis Jacob; Mikaela Bloomberg; Ian Danilevicz; Frank van der Heide; Séverine Sabia; Archana Singh-Manoux (GeroScience, 2025)
Chronic conditions and multimorbidity are increasingly prevalent in ageing populations, and their impact on disability remains poorly understood. This study investigated the association of chronic conditions and multimorbidity at ages 50, 60, 70, and 80 years with the subsequent onset of disability. Data from 108,810 participants (54% women, mean age 61.2 ± 9.8 at baseline) from the Health and Retirement Study, the English Longitudinal Study of Ageing, and the Survey of Health, Ageing, and Retirement in Europe were used. The number of chronic conditions was determined from a list of eight conditions. Cox regression was used to examine the incidence of disability in activities of daily living (ADL). ADL disability per 1000 person-years was 14.2 (13.7, 14.7) at age 50, 22.4 (21.9, 22.9) at age 60, 34.3 (33.4, 35.1) at age 70, and 67.6 (65.6, 69.6) at age 80. Having one chronic condition at age 50 was associated with a hazard ratio (HR) for ADL disability of 1.50 (1.42, 1.58) and 1.22 (1.13, 1.42) at age 80. For individuals with three or more chronic conditions, the HRs were 3.05 (2.79, 3.33) at age 50 and 1.74 (1.61, 1.87) at age 80. Analysis of population attributable fraction suggests that between 5.0 and 29.4% of incident disability, depending on the intervention scenarios and age at onset of chronic diseases, could be reduced by acting on chronic diseases. Chronic conditions and multimorbidity demonstrated a strong association with the onset of ADL disability, highlighting the need for early intervention to mitigate future disability risks.

Correction to: Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)

Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)
Rationale Psilocybin is a potentially paradigm-shifting depression intervention. We conducted a systematic review and meta-analysis of psilocybin-for-depression randomized controlled trials (RCTs). Objectives Systematically assess harm reporting, risk of bias, action mechanism specification, and incremental therapeutic effect sizes in the psilocybin-for-depression RCT literature. Methods Assessed databases included PsycINFO, CINAHL, Embase, Medline, Web of Science, and Scopus. Search terms “Psilocybin” or “Psychedelic” were paired with “Depression”, and "Randomized Controlled Trial" or “RCT”. Results We identified k = 9 RCTs ( k = 10 subgroups) involving n = 602 participants (56% psilocybin). Five studies had low/very low harm quality reporting, opposed to two with high. Most studies demonstrated a high risk of bias. Therapeutic mechanisms of action (MoAs) were discussed in varying detail but rarely assessed in original publications. Psilocybin was moderately superior to controls at reducing depression ( g = 0.62; 95% CI = 0.27, 0.98). Effects were heterogenous (τ = .47). Smaller studies evidenced stronger effects that favored psilocybin (Egger’s b 0 = 3.63, p = .014). Almost all studies documented financial conflicts of interests. Conclusion Psilocybin demonstrates significant depression reduction relative to controls. However, researchers, clinicians, and stakeholders should consider several contextual factors. Effects were moderate and attenuated in larger and better-controlled studies. Harms reporting and risk of bias was high, though partly driven by unique challenges of psilocybin research. MoAs were variably specified but rarely assessed; suggesting it is unclear how depression is reduced. We advise researchers conduct RCTs with active control conditions, larger samples, and include MoA assessments. Independent RCTs from researchers without financial conflicts of interest are needed.

Conflict at work and incident chronic low back pain: a retrospective cohort of more than 101,000 adults from Germany - Karel Kostev; Dong Keon Yon; Razak M. Gyasi; André Hajek; Louis Jacob (International Archives of Occupational and Environmental Health, 2025)

An integrated high-rate algal pond ̶ immobilized algal biomat reactor (HRAP ̶ IAB) for rapid phycoremediation and biomass production – A loop and non-retrofit approach - Judah Jacob; Allwin Vinoth Jayakumar; Varshavardhini Moorthy; Poonam Marcella Andrew Louis; Samson Lijoseraj Charles; Jayandan Sellapillai Arunachalam; Muthu Thangavel; Ramasamy Vijayaraghavan; Senthil Chinnasamy; Polur Hanumantha Rao (Journal of Water Process Engineering, 2025)

Shell temperature: How shall we tell if a still gosling is under the eggshell? - Valeriy G. Narushin; Michael N. Romanov; Louis Gressier; Elouann Jacob; Attila Salamon; Sabine Klein; John P. Kent (Theriogenology, 2024)

First Azygiid Reported from Africa or a Characiform Fish: Plenivitellinum kifi n. gen., n. sp. (Digenea: Azygiidae) Infecting the Gut of African Tigerfish, Hydrocynus vittatus Castelnau, 1861 (Characiformes: Alestidae) from the Kavango River - Triet Nhat Truong; Haley Rebecca Dutton; Edward Charles Netherlands; Louis Heyns DuPreez; Francois Jakob Jacobs; Stephen Ashton Bullard (Acta Parasitologica, 2024)

Mobilization rates of landslides in a changing tropical environment: 60-year record over a large region of the East African Rift - Arthur Depicker; Gerard Govers; Liesbet Jacobs; Matthias Vanmaercke; Judith Uwihirwe; Benjamin Campforts; Désiré Kubwimana; Jean-Claude Maki Mateso; Toussaint Mugaruka Bibentyo; Louis Nahimana; Benoît Smets; Olivier Dewitte (Geomorphology, 2024)

Predicting preincubation parameters in goose eggs to reduce their hatching waste - Valeriy G. Narushin; Michael N. Romanov; Louis Gressier; Elouann Jacob; Attila Salamon; John P. Kent (Biosystems Engineering, 2023)

Transgenic direct terminal repeats of Dissociation (Ds) produce chromosomal breakage in maize - Lakshminarasimhan Krishnaswamy; Changzeng Zhao; Patrice S. Albert; Zhi Gao; Ellen Mazalale; Alessandra Torno York; Louis Nastasi; Jacob A. Kelly; Hua Yang; James A. Birchler (The Nucleus, 2023)
Barbara McClintock recognized transposable elements originally by the movement of a site of chromosomal breakage, a genetic element called Dissociation ( Ds ) that was induced to break or transpose by another element she called Activator . The chromosome breaking version, when analyzed on the molecular level was one transposon inside another. It is now known that transposition involving transposon termini in non-standard orientation with reference to each other results in chromosomal breakage. Here we used engineered transposon ends together with a phenotypic marker to cause targeted chromosomal breaks. The results indicate that engineered direct orientation of the naturally inverted repeats of Dissociation can cause chromosomal breakage at the transgenic sites of insertion.

Evaluating a short vs. long-term progeny test and investigating physiology associated with survival in extreme low salinity for the eastern oyster Crassostrea virginica - Alexandra J. McCarty; Shannon Hood; Klaus Huebert; Jacob Cram; Katherine McFarland; Louis V. Plough (Aquaculture, 2023)

Prevalence of and factors associated with long-term sick leave in working-age adults with osteoarthritis: a retrospective cohort study conducted in Germany - Louis Jacob; Ai Koyanagi; Josep Maria Haro; Jae Il Shin; Lee Smith; Marcel Konrad; Karel Kostev (International Archives of Occupational and Environmental Health, 2023)

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Prevalence of and factors associated with long-term sick leave in working-age adults with chronic low back pain in Germany - Louis Jacob; Ai Koyanagi; Lee Smith; Jae Il Shin; Josep Maria Haro; Tilman Garthe; Karel Kostev (International Archives of Occupational and Environmental Health, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Chronic productive cough and inhalant occupational exposure–a study of the general population - Stinna Skaaby; Esben Meulengracht Flachs; Peter Lange; Vivi Schlünssen; Jacob Louis Marott; Charlotte Brauer; Børge G. Nordestgaard; Steven Sadhra; Om Kurmi; Jens Peter Ellekilde Bonde (International Archives of Occupational and Environmental Health, 2021)

Ancient Anthropogenic Clam Gardens of the Northwest Coast Expand Clam Habitat - Dana Lepofsky; Ginevra Toniello; Jacob Earnshaw; Christine Roberts; Louis Wilson; Kirsten Rowell; Keith Holmes (Ecosystems, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Persistence and treatment-free interval in patients being prescribed biological drugs in rheumatology practices in Germany - Karel Kostev; Louis Jacob (European Journal of Clinical Pharmacology, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Landslide inventory for hazard assessment in a data-poor context: a regional-scale approach in a tropical African environment - Elise Monsieurs; Liesbet Jacobs; Caroline Michellier; Joseph Basimike Tchangaboba; Gloire Bamulezi Ganza; Francois Kervyn; Jean-Claude Maki Mateso; Toussaint Mugaruka Bibentyo; Christian Kalikone Buzera; Louis Nahimana; Aloys Ndayisenga; Pascal Nkurunziza; et al. (Landslides, 2018)

Chemical regulation of body feather microbiota in a wild bird - Staffan Jacob; Louis Sallé; Lucie Zinger; Alexis S. Chaine; Christine Ducamp; Léa Boutault; Andrew F. Russell; Philipp Heeb (Molecular Ecology, 2018)
The microbiota has a broad range of impacts on host physiology and behaviour, pointing out the need to improve our comprehension of the drivers of host–microbiota composition. Of particular interest is whether the microbiota is acquired passively, or whether and to what extent hosts themselves shape the acquisition and maintenance of their microbiota. In birds, the uropygial gland produces oily secretions used to coat feathers that have been suggested to act as an antimicrobial defence mechanism regulating body feather microbiota. However, our comprehension of this process is still limited. In this study, we for the first time coupled high‐throughput sequencing of the microbiota of both body feathers and the direct environment (i.e., the nest) in great tits with chemical analyses of the composition of uropygial gland secretions to examine whether host chemicals have either specific effects on some bacteria or nonspecific broad‐spectrum effects on the body feather microbiota. Using a network approach investigating the patterns of co‐occurrence or co‐exclusions between chemicals and bacteria within the body feather microbiota, we found no evidence for specific promicrobial or antimicrobial effects of uropygial gland chemicals. However, we found that one group of chemicals was negatively correlated to bacterial richness on body feathers, and a higher production of these chemicals was associated with a poorer body feather bacterial richness compared to the nest microbiota. Our study provides evidence that chemicals produced by the host might function as a nonspecific broad‐spectrum antimicrobial defence mechanism limiting colonization and/or maintenance of bacteria on body feathers, providing new insight about the drivers of the host's microbiota composition in wild organisms.

Risk of depression, anxiety, and adjustment disorders in women with a suspected but unconfirmed diagnosis of breast or genital organ cancer in Germany - Karel Kostev; Louis Jacob; Matthias Kalder (Cancer Causes & Control, 2017)

Spontaneous imbibition of water and determination of effective contact angles in the Eagle Ford Shale Formation using neutron imaging - Victoria H. DiStefano; Michael C. Cheshire; Joanna McFarlane; Lindsay M. Kolbus; Richard E. Hale; Edmund Perfect; Hassina Z. Bilheux; Louis J. Santodonato; Daniel S. Hussey; David L. Jacobson; Jacob M. LaManna; Philip R. Bingham; et al. (Journal of Earth Science, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Opsin Genes and Visual Ecology in a Nocturnal Folivorous Lemur - Carrie C. Veilleux; Rachel L. Jacobs; Molly E. Cummings; Edward E. Louis; Deborah A. Bolnick (International Journal of Primatology, 2014)

The MISTIGRI thermal infrared project: scientific objectives and mission specifications - Jean-Pierre Lagouarde; Michel Bach; José A. Sobrino; Gilles Boulet; Xavier Briottet; Selma Cherchali; Benoit Coudert; Isabelle Dadou; Gérard Dedieu; Philippe Gamet; Olivier Hagolle; Frédéric Jacob; et al. (International Journal of Remote Sensing, 2013)

Factors affecting male and female reproductive success in a chipmunk (Tamias sibiricus) with a scramble competition mating system - Julie Marmet; Benoît Pisanu; Jean-Louis Chapuis; Gwenaël Jacob; Emmanuelle Baudry (Behavioral Ecology and Sociobiology, 2012)

Computing with bacterial constituents, cells and populations: from bioputing to bactoputing - Vic Norris; Abdallah Zemirline; Patrick Amar; Jean Nicolas Audinot; Pascal Ballet; Eshel Ben-Jacob; Gilles Bernot; Guillaume Beslon; Armelle Cabin; Eric Fanchon; Jean-Louis Giavitto; Nicolas Glade; et al. (Theory in Biosciences, 2011)

Social Network Influences Decision Making During Collective Movements in Brown Lemurs (Eulemur fulvus fulvus) - Armand Jacobs; Cédric Sueur; Jean Louis Deneubourg; Odile Petit (International Journal of Primatology, 2011)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

Mild opioid deprivation increases the degree that opioid-dependent outpatients discount delayed heroin and money - Louis Giordano; Warren Bickel; George Loewenstein; Eric Jacobs; Lisa Marsch; Gary Badger (Psychopharmacology, 2002)

New Cases of Mokola Virus Infection in South Africa: A Genotypic Comparison of Southern African Virus Isolates - Louis Nel; Jeanette Jacobs; Julian Jaftha; Beate von Teichman; John Bingham (Virus Genes, 2000)

Natural Spillover of a Distinctly Canidae-Associated Biotype of Rabies Virus into an Expanded Wildlife Host Range in Southern Africa - Louis Nel; Jeanette Jacobs; Julian Jaftha; Courteney Meredith (Virus Genes, 1997)